2010
DOI: 10.1007/s11581-010-0466-6
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the electronic conductivities of In-doped CaZrO3 by a DC polarization technique

Abstract: The following hydrogen and oxygen concentration cells using the oxide protonic conductors, CaZr 0:98 In 0:02 O 3Àd and CaZr 0:9 In 0:1 O 3Àd , as the solid electrolyte were constructed, and their polarization behavior was studied,The characteristics between applied voltages and external currents (V-I characteristics) in a DC polarization state were studied at 1,173 to 1,273 K in various atmospheres at the side of the reversible electrode. From the obtained atmosphere dependence of the steady-state current, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
(27 reference statements)
1
3
0
1
Order By: Relevance
“…On the other hand, Yamaguchi et al 12 reported that the excess negative charge of dopant ions(In 0 zr ) was fully compensated by dissolved protons in 1 mol % In-doped CaZrO 3 under a water-vapor-containing atmosphere. However, we confirmed 13,14 that the ratio of the concentration of protons to indium ion decreased with the increasing concentration of indium ions in CaZrO 3 . Furthermore, we clarified that the proton concentration in 2 mol %In-doped CaZrO 3 was about 2% by an evaluation based on the conductivity and the proton mobility determined from the relaxation process of the H þ =D þ isotope effect on the conductivity.…”
Section: Theorysupporting
confidence: 75%
See 2 more Smart Citations
“…On the other hand, Yamaguchi et al 12 reported that the excess negative charge of dopant ions(In 0 zr ) was fully compensated by dissolved protons in 1 mol % In-doped CaZrO 3 under a water-vapor-containing atmosphere. However, we confirmed 13,14 that the ratio of the concentration of protons to indium ion decreased with the increasing concentration of indium ions in CaZrO 3 . Furthermore, we clarified that the proton concentration in 2 mol %In-doped CaZrO 3 was about 2% by an evaluation based on the conductivity and the proton mobility determined from the relaxation process of the H þ =D þ isotope effect on the conductivity.…”
Section: Theorysupporting
confidence: 75%
“…CaO and CaIn 2 O 4 phases are known to exist in the specimen of 10 mol % In-doped CaZrO 3 . 14 However, because their phases were distributed as small isolated islands, we assumed that they did not affect the emf properties of the matrix phase. The porous platinum electrodes were applied to both the inner and outer surfaces on the closed end of the sample tube to 10 mm length by coating with platinum paste and subsequent firing at 1123 K. Platinum lead wires were then attached to each electrode by sintering.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…При акцепторном допировании материалы на основе СаZrO 3 становятся протонными твердыми электролитами в широкой области pO 2 и температур, что является весьма привлекательным для практических приложений, в частности, для электрохимических датчиков [7,8]. Большое количество работ посвящено исследованиям твердых электролитов системы СаZr 1−x In x O 3−δ , в том числе в дейтерированных атмосферах [8][9][10]. Наличие высокого H/D-изотопного эффекта в ЭДС позволило создать электрохимический датчик для определения концентрации изотопов водорода в смеси газов H 2 + D 2 на основе электролита СаZr 0.90 In 0.10 O 3−α [8].…”
Section: Introductionunclassified
“…Among important materials that have attracted considerable attention, AZrO 3 zirconate perovskites (A = Pb, Ca, Sr, and Ba) have been used in several technological applications as electronic conductors, proton conductors, memory devices, thermal barriers, electronic devices, high-voltage applications, radioluminescence, and photoluminescence. , In particular, BaZrO 3 (BZO) is characterized by a very high structural and thermal congruent melting point of about 2600 °C, with a small thermal expansion coefficient, and low thermal conductivity, besides excellent mechanical and structural integrity under extreme thermal conditions associated with high stability under severe heating. These exceptional properties lead to applications in electroceramics and refractaries and as a protective agent against corrosion of applied superconductors . To enhance their physical properties, the semiconductor, such as BZO, usually needs high crystallinity and various regular shapes.…”
Section: Introductionmentioning
confidence: 99%